Upregulated hsa_circ_0005785 Facilitates Cell Growth and Metastasis of Hepatocellular Carcinoma Through the miR-578/APRIL Axis - Wu, Anqi; Li, Yi; Kong, Mingzhu; Zhu, Baihui; Liu, Ruoyu; Bao, Fang; Ju, Shaoqing; Chen, Lin; Wang, Feng (Frontiers in Oncology, 2020)
Although accumulating documents have expounded the pivotal position of circular RNAs (circRNAs) in hepatocarcinogenesis and progression, the overwhelming majority of their functions and molecular mechanisms in hepatocellular carcinoma (HCC) are elusive. Herein, we explored the functions and potential mechanisms of hsa_circ_0005785 in HCC, which was aberrantly overexpressed in HCC and related to HCC patients’ TNM stage and overall survival. Moreover, hsa_circ_0005785 depletion could repress proliferation and metastasis of HCC cell in vitro, lead to cell apoptosis and cell cycle arrest, as well as restrain HCC cell growth in vivo. Furthermore, mechanism analyses discovered that hsa_circ_0005785 adsorbed miR-578 by playing a miRNA sponge role, which resulted in the derepression of a proliferation-inducing ligand (APRIL) expression, a miR-578’s mRNA target. Besides, hsa_circ_0005785 reversed the suppressive influence of miR-578 on HCC and accelerated tumor malignant progression through miR-578/APRIL axis. Taken together, our current study revealed an oncogenic role of hsa_circ_0005785 in the tumorigenesis of HCC. Moreover, targeting to the hsa_circ_0005785/miR-578/APRIL regulatory pathway might be a promising diagnostic and therapeutic strategy for HCC clinical practice.